Transformasi Layanan Pendidikan di MTs Swasta Batang Barat: Peran Komunikasi, Kompetensi, dan Etos Kerja Guru - Saputro, Arif Slamet; Nurkholis, Nurkholis; Abdullah, Ghufron (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to examine the effects of teacher communication behavior, professional competence, and work ethos on the quality of educational services in private MTs (Islamic junior high schools) within the Batang Barat district, Indonesia. The research addresses the extent to which these factors influence educational service quality, thereby contributing valuable insights into improving school standards to meet community expectations.Method – This quantitative study employed a survey approach, with data collected through validated questionnaires. The sample comprised 164 teachers from MTs Swasta Sub Rayon Batang Barat, selected through specific sampling techniques. Data were analyzed using simple and multiple regression analysis with SPSS version 26 to determine the individual and combined effects of the independent variables on the dependent variable. Findings – The results indicate that each independent variable—teacher communication behavior, professional competence, and work ethos—significantly affects the quality of educational services. Furthermore, a combined effect of these variables demonstrates a substantial influence on overall service quality, highlighting the critical role of teacher competencies and interpersonal skills in educational settings. Research Implications – These findings underscore the importance of enhancing teacher training and development programs focused on communication, competence, and work ethic, as these are fundamental to achieving high-quality educational services. The study offers actionable insights for educational administrators and policymakers in formulating strategies and policies to enhance teacher performance, ultimately fostering an improved educational environment aligned with community standards.